2016
DOI: 10.3390/polym8100349
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Compatibility, Hydrophilicity and Mechanical Properties of Polysulfone Ultrafiltration Membranes with Lignocellulose Nanofibrils

Abstract: Lignocellulose nanofibrils (LCN) and cellulose nanofibrils (CNF) are popular nanometer additives to improve mechanical properties and hydrophilic abilities; moreover, lignocellulose has potential as a natural adhesion promoter in fiber-reinforced composites. LCN and CNF were blended into polysulfone (PSF) to prepare ultrafiltration membranes via the phase inversion method. These additives were characterized by Fourier transform infrared spectroscopy and transmission electron microscopy, and the rheological pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…Therefore, it is necessary to enhance its mechanical property for long term operation and being subjected to high flow rates for wastewater treatment. Previous studies have reported several techniques to improve the mechanical properties of polymeric membranes such as plasma treatment, phase inversion, blending of cellulose nanofibrils with polymers, thermal treatment, and chemical modification . However, all these techniques either consume too much time or make membrane fabrication process complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to enhance its mechanical property for long term operation and being subjected to high flow rates for wastewater treatment. Previous studies have reported several techniques to improve the mechanical properties of polymeric membranes such as plasma treatment, phase inversion, blending of cellulose nanofibrils with polymers, thermal treatment, and chemical modification . However, all these techniques either consume too much time or make membrane fabrication process complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the agglomeration of nanoparticles caused blockage in some pores. [38] According to the EDS results ( Figure S2), the intensity of the silica nanoparticles embedded on the membrane surface increase based on the percentage of nanoparticles in the casting solution. There is a uniform distribution of nanoparticles on the surface of membranes at 0.25 and 0.5% of Si-MWCNT.…”
Section: Tg Analysismentioning
confidence: 97%
“…Among the PVC/Si-MWCNT nanocomposite membranes, PVC/0.5Si-MWCNT membrane had the largest pore diameter and also the highest surface porosity. [38] The changes in the membranes surface pore size and porosity might be attributed to the stronger hydrophilic nature of Si-MWCNT nanoparticles and the high casting solution viscosity, which accelerated the exchange rate between solvent and nonsolvent during the phase inversion which, in turn, led to a higher membrane porosity and a larger porous structure. [39,40] These results are also in accordance with the porosity and pore size data listed in Table 2.…”
Section: Tg Analysismentioning
confidence: 99%
“…The three-dimensional order (3D) microenvironment complexity contributes to regulate tumor growth in vivo [1,2,3,4]. In the liver tissue, hepatocytes are shaped in a single cord-like aggregate and connected by adjacent sinusoids [5,6,7,8]. Studies have been shown that hepatocytes cultured as spheroids have the ability to maintain long-term hepatic function and promote cell–cell communication and gap junction [9,10].…”
Section: Introductionmentioning
confidence: 99%